Drying patterns of nanofluid drops - Ow, Hui Ying. (2011)
Nanofluids are new kinds of fluids engineered by dispersing nanoparticles in base fluids. They are solutions containing suspended solid nanoparticles of size 1-100nm. This report investigates the nature of nanoparticles and their interaction with base liquids in single phase. Copper, graphite and titanium oxide nanoparticles are prepared in base fluid water. The effects of particle volume fraction, temperature and particle size on the dryout patterns will be investigated in this report. The main focus of the project will be on the study of the dryout pattern of dried nanofluid droplets. Dryout patterns for different mass concentrations of 25 nm copper nanoparticles in water range from 0.25g/l to 5g/l were studied. Sessile droplets of each solution and of different diameter varied from 0.1 mm to 1 mm, were placed on the silicon wafer and left for drying at the room temperature in natural conditions. The drying droplet was observed directly using the optical microscope and digital images of the process were captured continuously. Experimental results were recorded using the optical microscope and compared with the simulated pictures. After full drying of nanofluid, the nanoparticles are left on the substrate and can self-organize into different structures on the substrate. JEOL 5600LV Scanning Electron Microscope (SEM) is used to observe the dried-in structures of the droplets. The lattice gas model of nanofluid dewetting and particle self-organization was implemented into the MATLAB code.